Convergence from the Territorial Approach: Case of the Piura Region - Peru, period 2007-2019 - Suarez Guerrero, Marvin (2021)
The article analyzes the effect of municipal investment on the convergence conditions in district development in the Piura Region (Peru), during the period 2007-2019. Convergence is evaluated on the Human Development Index (HDI) from two approaches, the traditional one through the so-called beta convergence (absolute and conditional), and the distribution approach, through the variance of the HDI (sigma convergence) and autocorrelation spatial, to analyze the dynamic behavior of development in time and territory, respectively. The results allow to establish that there are no convergence conditions in the Piura region, given that the differences in the HDI between districts make an increase in the period analyzed and, in addition, there is statistical evidence of spatial autocorrelation (Moran's index and general G of Getis- Ord) in regional development, which is manifested in a polarization of the HDI between a developed cluster (urban) and a lagging one (rural). In addition, municipal investment efforts have been insufficient to reverse this dynamic, because its impact is limited by structural factors that strongly condition its development, such as persistent poverty, population density and vulnerability to natural phenomena.